DISPARITAS PENUNTUTAN PERKARA TINDAK PIDANA KORUPSI DI WILAYAH HUKUM KEJAKSAAN TINGGI RIAU - Tri Wulandari Adhyaksa; Mukhlis R; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Attorney who is given the authority to conduct the prosecution of corruption cases seem less than optimal so that corruption cases has increased from year to year , although in this case the criminal decisions handed down by the judge but the prosecutor gave the facts to the judge for a legal verdict . so the purpose of the imposition of criminal sanctions in an effort to tackle corruption cases do not provide a deterrent effect against perpetrators . In making the charges in several corruption cases , the public prosecutor in the case ensnare the perpetrators either same or different from the same article . As for the purpose of writing this thesis , namely : First , to know how to overcome the disparity of prosecution of corruption cases in the jurisdiction of the High Court of Riau , Second, to determine the Attorney constraints in conducting prosecution of corruption crimes in the jurisdiction of the High Court of Riau. The conclusion that can be derived from research First , to address the disparity in the prosecution of corruption cases that follow pidan : Creating Refers Charges In Law and Related Regulations , Guidelines for Criminal Prosecution , Directive Leadership . Second , constraints in doing Prosecution Attorney Corruption Case in High Court jurisdiction Riau , namely : first defendant Blurred / List People Search ( DPO ) and Decision of Judge Not Match With Prosecution Demands / straatmach .Keywords : Disparity in Criminal - Attorney - Prosecution - Corruption